Evaluasi Kegagalan Penawaran Kontraktor Pada Pelelangan Umum Pascakualifikasi Proyek Jalan Dan Gedung Tahun 2015 – 2017 Di Provinsi Riau - Riska Yulia; Rian Tri komara Iriana; Alfian Kamaldi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The success of the contractor in getting a job (project) can be seen in the process called tender. In tender phase, as a Presidential Regulation of The Republic of Indonesia Number 4 in 2015 explanation about government procurement. Generally, the stage of bid evaluation is divided into 4 stages, that are administrative evaluation stage, technical evaluation, price evaluation, and verification stages, all use an electronic procurement system called Layanan Pengadaan Secara Elektronik (LPSE). Based on the regulation above, this research purposes to find out the failure variables and the percentage of its variables in each process the construction services auction in government project, especially in Riau Province. The primary data that was obtained from the quetionnaire to contractor companies and interview with LPSE staff, and secondary data was obtained from the LPSE website of Riau Province, speficifically the auction of road and building project from 2015 to 2017. A certain spread sheet application program was used to calculate and analyze data, and presented in some bar charts. As the result, the dominant failure in the bid evaluation phase during 2015 to 2017 are, (1) Administrative evaluation: it does not fulfill the requirements for validity period of offering letter not less than the time as stated in the Election Document (27%), (2) Technical evaluation: the schedule for the execution of the work offered is not as stated in the Election Document (43%), (3) Price evaluation: it does not fulfill the lowest price requirements, so it cannot be evaluated, because it has already received 3 aritmethic lowest offer that passed the evaluation (69%), (4) evaluation of verification: it does not fulfill requirements attaching Quarry permit in accordance to requirements in bid documents (44%) and addendum and proof of completeness of minimum number of personnel (67%). Keywords: evaluation, failure, offering, auction, tender.